Compact shorted inverted‐L antenna with circular polarisation for RFID handheld reader. Issue 7 (1st March 2013) - Lin, Y.F.; Chen, H.M.; Chen, C.H.; Lee, C.H.
Abstract : Two shorted inverted‐L radiating elements are located on the orthogonal corner of the square substrate and connected to each output port of a Wilkinson power divider. A shorted inverted‐T strip is placed on the other corner of the square for a perturbing resonator to generate circularly‐polarised (CP) radiation in the UHF band. Proper adjusting of the horizontal and vertical lengths of the inverted‐T strip will differentiate two orthogonal linearly modes with 90° phase difference for a good CP radiation. Simulated and measured results indicate that the proposed structure can achieve circular‐degree polarisation operation. A measured impedance bandwidth (VSWR ≤ 2) of about 16.4% (810–960 MHz) and a 3 dB axial‐ratio (AR) bandwidth of about 4.4% (890–930 MHz) at 915 MHz were obtained.